2018
DOI: 10.3389/fphar.2018.01206
|View full text |Cite
|
Sign up to set email alerts
|

Da-Bu-Yin-Wan Improves the Ameliorative Effect of DJ-1 on Mitochondrial Dysfunction Through Augmenting the Akt Phosphorylation in a Cellular Model of Parkinson’s Disease

Abstract: Da-Bu-Yin-Wan (DBYW) is recorded originally in China over six centuries ago, and it is used to treat Parkinson’s disease (PD) clinically in recent decades. DJ-1 is a homodimeric protein linked to early-onset PD, and found in the mitochondria. In addition, DJ-1 could protect the cells by regulating gene transcription and modulating the Akt signal pathways. Therefore, in this research, we aimed to investigate the ameliorative effect of DBYW on mitochondria in the view of the DJ-1 and Akt signaling. Rat adrenal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The protective effects of BYQZF on mitochondrial function have been confirmed in in vitro and in vivo studies (Zhang et al, 2013;Zhang et al, 2018;Gai et al, 2019); parkin was found to play an important role in this process. However, the mechanisms by which BYQZF ameliorates mitochondrial dysfunction via parkin are unclear.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The protective effects of BYQZF on mitochondrial function have been confirmed in in vitro and in vivo studies (Zhang et al, 2013;Zhang et al, 2018;Gai et al, 2019); parkin was found to play an important role in this process. However, the mechanisms by which BYQZF ameliorates mitochondrial dysfunction via parkin are unclear.…”
Section: Discussionmentioning
confidence: 75%
“…Our previous studies showed that Da-Bu-Yin-Wan ameliorates MPTP-induced behavioral impairment, increases the expression of tyrosine hydroxylase in the substantia nigra, and prevents loss of substantia nigra dopaminergic neurons in a PD mouse model (Gong et al, 2014). Moreover, Da-Bu-Yin-Wan and/or Qian-Zheng-San significantly increase ATP levels and complex I activity in the midbrain tissue of PD model mice (Zhang et al, 2013), and BYQZF reduced mitochondrial damage and improved the mitochondrial morphological structure in a cellular model of PD (Zhang et al, 2018;Gai et al, 2019). These studies suggest that BYQZF had neuroprotective effects on mitochondrial function and may be applicable as a mitochondrion-targeted therapeutic drug for treating PD.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, DBYW was found to augment this process by enhancing the effects of DJ-1 on mitochondrial function through Akt phosphorylation. Additionally, DBYW enhances mitochondrial protection in PD by elevating cellular ATP content and decreasing the expression of ATP-sensitive potassium channel subunits [132].…”
Section: Da-bu-yin-wan (Dbyw)mentioning
confidence: 99%
“…Western Blot. Western blot was performed as described previously [35,36]. e total protein was extracted from SCs and transferred to polyvinyl difluoride (PVDF) membranes.…”
Section: Immunohistochemistrymentioning
confidence: 99%